Utility of MELD scoring system for assessing the prognosis of acute fatty liver of pregnancy. (September 2019) - Li, Ping; Lin, Shuo; Li, Ling; Cui, Jinhui; Wang, Qingqing; Zhou, Shuisheng; Fan, Jianhui
Abstract: Objective: To evaluate the value of Model for end-stage liver disease (MELD) in assessing the prognosis of acute fatty liver of pregnancy (AFLP). Study design: This was a retrospective study. From January 2010 to July 2018, data of 53 women diagnosed with AFLP in the third affiliated hospital of Sun Yat-Sen University were collected. Blood samples were collected on admission and MELD score was calculated. The MELD score was calculated by using the original MELD formula as shown: 9.57 log (creatinine) + 3.78 log (bilirubin) + 11.20 log (international normalized ratio, INR) + 6.43. The perinatal outcomes were documented. Results: Nine women were excluded as they were transfered to our hospital after delivery in other hospitals. The remaining 44 women had average age of 28.8 ± 5.2 years. The MELD score showed good performance in predicting most of the perinatal complications of AFLP with all the area under the receiver operating characteristic (ROC) curves (AUC) > 0.8, including ascites (AUC: 0.91, 95% CI: 0.78–0.98), wound seroma (AUC: 0.91, 95% CI: 0.78–0.93), hepatic encephalopathy (AUC: 0.93, 95% CI: 0.82–0.99), DIC (AUC: 0.87, 95% CI: 0.74–0.95), sepsis (AUC: 0.93, 95% CI: 0.82–0.99), renal insufficiency (AUC: 0.94, 95% CI: 0.82–0.99) and stillbirth (AUC: 0.85, 95% CI: 0.71–0.94). Nearly all the maternal complications were more frequently happened in MELD score ≥30 group ( P  < 0.05). Conclusion: MELD scoring system may be a suitable method for assessing the prognosis of AFLP.